SISTEM FONOLOGI BAHASA KODI DI PULAU SUMBA - Ekayani, Ni Putu (S2 Ilmu Linguistik Fakultas Ilmu Budaya Universitas Udayana, 2015)
This studyfocus on a languagein Sumba Island, the language of Kodi (BK). Twoissuesthatunderliethis study, namely(1) how the inventory ofphonemesinBKof Sumba Island, and(2) how the distinctivefeaturesof languagephonemeinventory of BK? Analyzeis donein the form of350BKlexicons, whichcapturedthroughunstructured interviewstofiveinformants who arenative speakers ofBK. By the generative phonology theory, thisqualitativestudyare summarizedintwofindings. First, that BKhas fivevowel phonemes/i, e, a,o, u/, withallophonesinthetwo, namelythe phoneme/e/withallophones[e] and[?] as well asthe phoneme/o/withallophones[o] and[?]. BKhas20consonant phonemes: /p, t, c, k, ?, ?, ?, ?, m, n, ?, mb, nd, nj, ng, l, h, r,w, y /. Sylabel pattern of BK is consist of minimum V (vocal) dan maximum CV (consonant+vocal), because this is a open vocalic language. Second, it can be concludedthat based on the basis ofdistinctivefeatures, phonemeson BKwasdivided intofivegroups (feature ofthe maincategories, placeof articulation, mannerof articulation, traitsstemtongue, andextra features) andtotaled18distinguishing features.